N-type flexible Bi2Se3 nanosheets/SWCNTs composite films with improved thermoelectric performance for low-grade waste-heat harvesting. (15th December 2022) - Zhang, Lin; Shang, Hongjing; Huang, Daxing; Xie, Bowei; Zou, Qi; Gao, Zhaoshun; Xue, Jiangli; Gu, Hongwei; Ding, Fazhu
Abstract: Due to the limited thermoelectric performance of polymers and intrinsic rigidness of inorganic materials, it is difficult to obtain n-type thermoelectric materials and devices with low-cost, excellent flexibility, and high performance. In this work, we have successfully synthesized n-type flexible free-standing thermoelectric films by a low-cost solvothermal method, which is composed of Bi2 Se3 nanosheets and single-wall carbon nanotubes (SWCNTs). Bi2 Se3 nanosheets with excellent crystallinity and rhombohedral morphology were grown on SWCNTs. The optimized Bi2 Se3 /SWCNTs composite films exhibited a high electrical conductivity of 292.7 S cm −1 and a Seebeck coefficient of − 42.4 μV K −1 at room temperature, eventually achieving an improved power factor of 52.7 μW m −1 K −2 . Furthermore, the composite films exhibited excellent flexibility due to the interweaving of Bi2 Se3 nanosheets with SWCNTs, where the thermoelectric performance remained almost unchanged after 5000 bending cycles around a 3.5 mm radius rod. A thermoelectric device, composed of the optimized films, was constructed to further show the practicality, which generated a voltage and a power density of 11.5 mV and 86.2 μW cm −2 at a temperature gradient of 58 K, respectively. This work can provide support for the preparation of other n-type free-standing thermoelectric films with both high thermoelectric performance and excellent flexibility. Graphical Abstract: ga1 Highlights: N-type flexible Bi2 Se3 /SWCNTs thermoelectric composite films have been successfully synthesized by a low-cost solvothermal method. The optimized composite films show high performance, which is the best among other Bi2 Se3 /CNTs flexible film materials. The thermoelectric performance remains almost unchanged after 5000 bending cycles around a 3.5 mm radius rod. A thermoelectric device assembled with eight-single-leg outputs 11.5 mV voltage and 86.2 μW cm −2 power density at a temperature gradient of 58 K.